Counting to perfect - LaFleur, Suzanne M (Wendy Lamb Books, an imprint of Random House Children's Books, 2018)
Ignored by her parents since her "perfect" older sister, Julia, had a baby, Cassie, twelve, foregoes her summer plans to join Julia and baby Addie on a road trip.